Chemistry and Bioactivity of NeoMTA Plus™ versus MTA Angelus® Root Repair Materials - Abu Zeid, Sawsan T.; Alamoudi, Najlaa M.; Khafagi, Monazah G.; Abou Neel, Ensanya A. (Journal of Spectroscopy, 2017)
Objectives. To analyse the chemistry and bioactivity of NeoMTA Plus in comparison with the conventional root repair materials. Method and Materials. Unhydrated and hydrated (initial and final sets) materials were analysed by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). For bioactivity study, small holes of dentin discs were filled with either materials, immersed in PBS for 15 days, and analysed with FTIR and scanning electron microscope with energy dispersive X-ray (SEM/EDX). The calculation of crystallinity and carbonate/phosphate (CO3/PO4) ratio of surface precipitates (from FTIR) and calcium/phosphate (Ca/P) ratio (from EDX) was statistically analysed using t-test or ANOVA, respectively, at 0.05 significance. Results. Both materials are tricalcium silicate-based that finally react to be calcium silicate hydrate. NeoMTA Plus has relatively high aluminium and sulfur content, with tantalum oxide as an opacifier instead of zirconium oxide in MTA Angelus. NeoMTA Plus showed better apatite formation, higher crystallinity and Ca/P but lower CO3/PO4 ratio than MTA Angelus. SEM showed globular structure with a small particle size in NeoMTA Plus while spherical structure with large particle size in MTA Angelus. Conclusion. Due to fast setting, higher crystallinity, and better bioactivity of NeoMTA Plus, it can be used as a pulp and root repair material.